Proton and photon radiosensitization effects of niraparib, a PARP‐1/‐2 inhibitor, on human head and neck cancer cells. Issue 9 (23rd April 2020) - Wang, Li; Cao, Jianzhong; Wang, Xiaochun; Lin, Eric; Wang, Zeming; Li, Yuting; Li, Yupeng; Chen, Mei; Wang, Xianliang; Jiang, Bo; Zhang, Ruiping; Sahoo, Narayan; et al.
Abstract: Background: Combining photon or proton radiotherapy with targeted therapy shows promise for head and neck cancer (HNSCC). The poly (adenosine diphosphate [ADP]‐ribose) polymerase‐1/2 inhibitor niraparib targets DNA damage repair (DDR). We evaluated the effects of niraparib in combination with photons or protons, and its effects on the relative biological effectiveness (RBE) of protons, in human HNSCC cell lines. Methods: Radiosensitivity was assessed and RBE was calculated with clonogenic survival assays; unrepaired DNA double‐strand breaks were evaluated using immunocytochemical analysis of 53BP1 foci. Results: Niraparib reduced colony formation in two of the four cell lines tested ( P < .05), enhanced radiosensitivity in all four cell lines, delayed DDR ( P < .05), and increased proton vs photon RBE. Conclusion: Niraparib enhanced the sensitivity of four HNSCC cell lines to both photons and protons and increased the RBE of protons, possibly by inhibiting DDR. Niraparib may enhance the effectiveness of both photon and proton radiotherapy for patients with HNSCC.